Animals, Relations, and the Laissez-Faire Intuition. (1st August 2016) - Hedberg, Trevor
Abstract : In Animal Ethics in Context, Clare Palmer tries to harmonise two competing approaches to animal ethics. One focuses on the morally relevant capacities that animals possess. The other is the Laissez-Faire Intuition (LFI): the claim that we have duties to assist domesticated animals but should (at least generally) leave wild animals alone. In this paper, I critique the arguments that Palmer offers in favour of the No-Contact LFI - the view that we have ( prima facie ) duties not to harm wild animals but no duties to assist them. I argue that Palmer's endorsement of the No-Contact LFI is unwarranted. Her arguments actually provide strong reasons to endorse what I call the Gradient View - a position that posits weak presumptive duties to assist wild animals that become stronger as our relations with the animals grow stronger.